Introduction of a safety checklist for gynecological laparoscopy - Silva, Dhammike; Randombage, Prabath; Gankanda, Wedisha (International Surgery Journal, 2020)
This study focuses on the importance of a safety checklist for gynecological laparoscopic surgeries. There is no dedicated safety check list for gynecological laparoscopy although several general safety checklists are used in practice. (e.g. WHO safety check list). The aim was to introduce a safety check list dedicated to gynecological laparoscopy. This check list is based on our experience in performing gynecological laparoscopy in a tertiary care centre with a high workload. This check list is introduced after studying the complications occurring in areas covered by the check list. Present data from 776 cases performed over 4 years at professorial unit in obstetrics and gynecology, university of Sri Jayewardenepura, Colombo South teaching hospital, Kalubowila, Sri Lanka. Mean surgical time and complications associated with patient positioning were assessed. Complications associated with the areas assessed were found to be low. However, it is belief that these can be further reduced by the introduction of a check list specifically designed for gynecological laparoscopy.